2020
DOI: 10.1080/25785826.2020.1776079
|View full text |Cite
|
Sign up to set email alerts
|

T follicular helper cell subsets: a potential key player in autoimmunity

Abstract: Follicular helper T (Tfh) cells are one of CD4þ helper T subsets which promote B cell maturation, activation and antigen-specific antibody production. Autoantibodies are hallmarks of autoimmune diseases, and crucial contributions of Tfh cells in development of these diseases are now evident. Deregulation of Tfh activities can contribute to a pathogenic autoantibody production and can play an important role in the promotion of autoimmune diseases. These days multiple researchers reported three subpopulations wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 95 publications
(143 reference statements)
1
40
1
1
Order By: Relevance
“…These fates determine the roles of terminal Tfh cells in the immune response. The Tfh1 differentiation pathway can be initiated by type 1 responses in which STAT1/4-activating cytokines expand, such as viral infection, vaccination, or some autoimmune diseases ( 9 , 10 , 12 , 13 ). Tfh1-source subsets produce IFN-γ and IL-21 and lead to isotype switching of GC B cells to induce murine IgG 2 or human IgG 1 ( 14 ).…”
Section: Functional Diversity Of Tfh Cellsmentioning
confidence: 99%
“…These fates determine the roles of terminal Tfh cells in the immune response. The Tfh1 differentiation pathway can be initiated by type 1 responses in which STAT1/4-activating cytokines expand, such as viral infection, vaccination, or some autoimmune diseases ( 9 , 10 , 12 , 13 ). Tfh1-source subsets produce IFN-γ and IL-21 and lead to isotype switching of GC B cells to induce murine IgG 2 or human IgG 1 ( 14 ).…”
Section: Functional Diversity Of Tfh Cellsmentioning
confidence: 99%
“…And even if Tfh cells are needed—will they develop from naïve T cells, or could other T‐helper lineages develop into Tfh cells in MALT? Different types of Tfh cells that share phenotype with other lineages have been described, making them Tfh1, Tfh2, or Tfh17 cells; do these develop when Tfh cells differentiated toward other phenotypes or do Th1, Th2, and Th17 cells become Tfh cells 173,174 . And what about T follicular regulatory (Tfr) cells—they seem to develop primarily from thymic T regulatory cells but can they also be derived from induced regulatory T cells or even naïve cells 175 …”
Section: T Cells Contributing To Iga Responsesmentioning
confidence: 99%
“…This will ultimately lead to immunoglobulin isotype switching and the production of long-lasting plasma cells. It has been shown that the frequency of Tfh cells is correlated with lymphocytic infiltration, the number of B cells, elevated serum and salivary gland Ig levels, and autoimmunity [ 68 , 69 ]. Tfh cells can also be found in the peripheral circulation and can be identified by CXCR5 expression on CD4 T-cells with flow cytometry [ 13 ].…”
Section: Immune Monitoring—the “How”mentioning
confidence: 99%